A China-Based exploration of surgical timing for polytrauma with a focus on fracture reconstruction - Chenning Ding; Mingwang Jia; Xing Han; Jiahui Zhang; Xin Zhao; Xiguang Sang (World Journal of Emergency Surgery)
Abstract Background For patients with severe polytrauma and fractures, early fracture reconstruction surgery under stable conditions can significantly reduce pulmonary and other complications. However, premature surgical intervention may heighten infection risk, adversely affecting the patient’s prognosis. Consequently, determining the optimal timing of surgery is crucial for patients with multiple traumatic injuries. Given China’s healthcare context, this study will assess injury severity and perform definitive fracture reconstruction at specified post-trauma intervals. Postoperative infection rates, including wound infections, other complication incidences, hospital stay duration, treatment costs, and long-term outcomes will be observed and compared to identify the optimal timing for surgical intervention. This study also aims to develop effective polytrauma management models. By applying accessible criteria and choosing suitable timing for fracture reconstruction, we can better assess patient conditions, reduce complications, and minimize the surgery’s “second hit” effect, addressing an important research gap regarding optimal surgical timing for polytrauma in China. Methods This study collected data on 200 patients treated at our hospital between March 2023 and March 2024, with an average age of 47.24 ± 16.56 years and an average Injury Severity Score (ISS) of 25.85 ± 13.35. A total of 250 fractures received definitive fixation in the initial surgery, including femoral fractures (n = 75), spinal fractures (n = 46), pelvic ring fractures (n = 49), tibial fractures (n = 25), acetabular fractures (n = 12), humeral fractures (n = 12), and other fractures (n = 5) (including clavicle, radius and ulna, calcaneus, and patella). Among these patients, 151 underwent single-fracture reconstruction, 42 had two fractures reconstructed, and 5 had three fractures treated during the first surgery. The study protocol excluded patients with absolute contraindications, including bacteremia and infections near the surgical site. Additional inclusion criteria required stable vital signs (temperature < 38.5 °C with a downward trend, systolic blood pressure > 100 mmHg, stable traumatic brain injury status) and blood routine (white blood cell count < 22.0 × 10⁹/L with a neutrophil percentage < 90%, both trending downward; platelet count > 50 × 10⁹/L; hemoglobin > 90 g/L). Based on these criteria, historical cohorts were identified and assigned to either an experimental group or a control group. Observed outcomes included postoperative complications, wound healing grades, inflammatory markers, changes in vital signs, length of hospital stay, costs, and long-term follow-up results. Results Among the patients, 97 underwent surgery after meeting the specified criteria for fracture reconstruction, while 103 received surgery without meeting these criteria. Patients who met the surgical criteria demonstrated superior outcomes, with lower complication rates (including pneumonia and respiratory distress syndrome), improved surgical incision healing, faster postoperative consciousness recovery, shorter overall and ICU stays, reduced hospitalization costs, greater joint mobility at the 9-month follow-up, and higher quality of life assessments compared to those who did not meet the criteria. Among patients who met the criteria, those with spinal fractures experienced better quality of life outcomes, and those with femoral fractures showed improved fracture healing. Conclusions For polytrauma patients with fractures, performing surgery once surgical requirements are met results in fewer early postoperative pulmonary complications, quicker recovery of consciousness, lower wound infection rates, shorter hospital and ICU stays, reduced costs, and improved postoperative outcomes. This protocol is safe and effective for most polytrauma patients requiring fixation, particularly those with mechanically unstable femoral, pelvic, acetabular, or spinal fractures.